2000
DOI: 10.1046/j.1365-2893.2000.00227.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus co‐infection is a negative prognostic factor for clinical evolution in human immunodeficiency virus‐positive patients

Abstract: A longitudinal study of human immunodeficiency virus (HIV)-infected individuals followed-up in 13 centres was performed to assess the influence of hepatitis C virus (HCV) on the clinical and immunological evolution of HIV-infected patients. Eight-hundred and twelve HIV-infected patients with known HIV acquisition date, 89 co-infected with HCV, were included in the cohort. Clinical progression was defined as: 30% decrease of Karnofsky's index; and/or 20% body weight loss; and/or acquired immune deficiency syndr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
1
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 17 publications
3
30
1
3
Order By: Relevance
“…The low frequency found in our study could be explained by the low incidence of intravenous drug use and the infrequent transfusions in this population, which are very different to those reported in the studies cited from Latin America where intravenous drug use 13,18,25 and past history of transfusion 7 were the main risk factors identified for HCV infection in HIV patients.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The low frequency found in our study could be explained by the low incidence of intravenous drug use and the infrequent transfusions in this population, which are very different to those reported in the studies cited from Latin America where intravenous drug use 13,18,25 and past history of transfusion 7 were the main risk factors identified for HCV infection in HIV patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Some studies have associated HCV coinfection with a faster HIV progression, although this conection is controversial 5,18,[21][22][23]30 . HCV infection also increases the toxicity to antiretroviral medications 9,18,26,27,32 .…”
Section: Introductionmentioning
confidence: 99%
“…The spontaneous clearance of chronic HCV infection is rare in monoinfection and probably even more so in HIV-1-coinfected subjects, although a few such cases have been described (8,10,30). Interestingly, some studies suggest that HCV/HIV-1 coinfection is associated with an increased rate of HIV-1 disease progression (14,22,24).…”
mentioning
confidence: 99%
“…Some studies suggest that this is also true for HIV-1 disease (14,22,24), although this is not observed in all cohorts (28). The high levels of immune activation may contribute to high rates of viral disease progression by impairing the ability of the immune system to respond.…”
mentioning
confidence: 99%
“…Compared to HCV mono-infected patients, co-infected individuals are also less likely to achieve viral clearance, and have higher HCV viral loads and more frequent HCV relapses after anti-HCV therapy [8][9][10][11]. Similarly, the possible role of HCV to accelerate HIV disease progression has also been reported by previous studies, which have shown the impaired CD4+ T cell count recovery during HAART, higher risk of AIDS, and liver disease-related deaths in co-infected individuals in comparison to HIV mono-infected ones [12][13][14][15][16][17][18][19]. Moreover, adverse drug reactions to HAART such as rash and hepatoxicity in HIV patients are exacerbated in coinfected patients, making the virological control of HIV harder to achieve [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 86%